'We will never give up': a qualitative study of ethical challenges Syrian health workers face in situations of extreme violence. Issue 2 (7th March 2022) - Singh, Namrita S.; Redman, Brittany; Broussard, Grant; DeCamp, Matthew; Rayes, Diana; Ho, Lara S.; Robinson, W. Courtland; Sankari, Abdulghani; Maziak, Wasim; Rubenstein, Leonard
Abstract : Active conflict settings constitute challenging operating environments for humanitarian health organisations and workers. An emerging feature of some conflicts is direct violence against health workers, facilities, and patients. Since the start of the war in 2011, Syria has endured extreme and deliberate violent attacks on health facilities and workers. This paper reports on the findings from a qualitative study that examined the lived experiences of Syrian humanitarian health workers facing extreme ethical challenges and coping with moral distress. In‐depth interviews were carried out with 58 front‐line health workers in north‐western and southern Syria. Participants described a number of ethical and operational challenges experienced while providing services in extreme conditions, as well as strategies used to deal with them. The complex intersection of personal and organisational challenges is considered and findings are linked to key ethical and humanitarian principles. Both practical recommendations and action steps are provided to guide humanitarian health organisations. نبذة مختصرة: تمثل بيئات الصراع النشطة بيئات عمل صعبة للمنظمات الصحية الإنسانية والعاملين فيها. ومن السمات الناشئة لبعض النزاعات العنف المباشر ضد العاملين الصحيين والمرافق الصحية والمرضى. تعرضت سوريا لهجمات عنيفة شديدة ومتعمد على المرافق الصحية والعمال منذ بداية الحرب في 2011. يُقدم هذا البحث نتائج دراسية نوعية بحثت التجارب التي عايشها العاملون الصحيون في المجال الإنساني السوري الذين يواجهون تحديات أخلاقية بالغة لمواجهة الكارثة الأخلاقية. أجريت مقابلات معمقة مع 58 من العاملين الصحيين في الخطوط الأمامية في شمال وجنوب سوريا. وصف المشاركون عدد من التحديات الأخلاقية والتشغيلية التي يواجهونها أثناء تقديم الخدمات في الظروف القاسية، فضلًا عن الاستراتيجيات المستخدمة لمواجهتهم. يتم النظر في التداخل المعقد بين التحديات الشخصية والتنظيمية، وترتبط النتائج بالمبادئ الأخلاقية والإنسانية الرئيسية. تُقدم توصيات عملية وخطوات عمل لتوجيه المنظمات الصحية الإنسانية. كلمات دليلية; مساعدة، صراع، أخلاق، صحة إنسانية، نوعية، سوريا، عنف 摘要: 在充满纷争的环境下，人道卫生组织和工作人员的工作极具挑战性。卫生工作者、设施和患者遭受到直接暴力冲突。自 2011 年叙利亚战争开始以来，叙利亚的医疗机构和工作人员不断遭到蓄意的极端暴力袭击。本文报告了一项定性研究的结果，该研究调查了叙利亚人道主义卫生工作者面对极端道德挑战、应对道德困境的经历。作者对叙利亚北部和南部的 58 名前线卫生工作者进行了深入访谈。他们讲述了在极端条件下工作时，遇到的道德挑战和工作挑战，以及应对这些挑战的策略。作者考虑到个人挑战和团队挑战穿插起来的难点，并将调查结果与关键的道德规范和人道主义原则联系起来。本文为人道主义卫生组织提供了一些实用的建议和行动步骤。 关键词：援助、冲突、伦理、人道主义健康、定性、叙利亚、暴力